ANALISIS KOMPONEN KIMIA DARI KAYU SENGON DAN KAYU KARET PADA BEBERAPA MACAM UMUR - Gustan Pari (Pusat Penelitian dan Pengembangan Hasil Hutan, 1996)
This paper reported the result of chemical analysis from sengon (Paraserianthes falcataria) and rubber wood (Hevea brasiliensis) with several age groups. The analysis comprise of the determination of holocellulose, cellulose, lignin, pentosan, ash content, silica content and the solubility in cold water, hot water, one percent of sodium hydroxide and alcohol benzene ex-tractives. These analysis were conducted to determine their basic characteristics and ultimate uses of the wood.The result showed that holocellulose content ranges from 66,46 - 70,90 % , cellulose from 46,62 - 49,88 %, lignin from 29,10 - 33,54 %, pentosan from 15,51 - 17,80 %, ash content from 0,45 - 1,25 %, silica content from 0,24 - 0,52 %, The solubility in cold water ranges from 3,12 - 5,40 %, hot water from 3,89 - 5,65 %, in NaOH 1 % from 13,06 - 16,06 % and in alcohol benzena (1:2)from 2,06 - 4,43 %. .Based on chemical analysis, especially the cellulose, lignin and pentosan content sengon and rubber wood are suitable as raw material for pulp and paper industry, except for 20 years old rubber wood.